2004
DOI: 10.1186/1477-7827-2-55
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotropin administration is associated with high pregnancy rates during ovarian stimulation and timed intercourse or intrauterine insemination

Abstract: Background: There are different factors that influence treatment outcome after ovarian stimulation and timed-intercourse or intrauterine insemination (IUI). After patient age, it has been suggested that timing of insemination in relation to ovulation is probably the most important variable affecting the success of treatment. The objective of this study is to study the value of human chorionic gonadotropin (hCG) administration and occurrence of luteinizing hormone (LH) surge in timing insemination on the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…Notably, ovulation induction with HCG was another factor that was significantly associated with clinical pregnancy after IUI. This is in accordance with previous studies [ 26 , 27 ]. After multivariate analysis, the parameter “male factor” differed only by trend (p = 0.067) between patients who achieved a clinical pregnancy and those who did not.…”
Section: Discussionsupporting
confidence: 94%
“…Notably, ovulation induction with HCG was another factor that was significantly associated with clinical pregnancy after IUI. This is in accordance with previous studies [ 26 , 27 ]. After multivariate analysis, the parameter “male factor” differed only by trend (p = 0.067) between patients who achieved a clinical pregnancy and those who did not.…”
Section: Discussionsupporting
confidence: 94%
“…They concluded that there seems to be no significant difference between doing IUI from 24 to 48 hours after hCG injection ( 18 ). Some other studies have mentioned the same conclusion ( 12 , 17 , 28 ) .…”
Section: Discussionsupporting
confidence: 62%
“…Natural ovulation usually occurs 37 to 39 hours after the start of luteinizing hormone surge ( 11 ). Follicular rupture and ovulation usually occur 36 to 38 hours after hCG injection ( 12 ). The optimal timing of IUI for improving pregnancy outcome has been mentioned 12, 18, 36-40 hours after hCG injection ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study by Taerk et al reported that hCG administration significantly increased clinical pregnancy rates compared with monitoring of spontaneous serum LH surge in subfertile patients undergoing controlled ovarian hyperstimulation IUI cycles (22). Two additional retrospective studies of stimulated IUI have also reported that higher pregnancy rates resulted when hCG was given to trigger ovulation (23,24).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies of ovarian hyperstimulation IUI cycles have demonstrated beneficial effects of hCG administration on IUI pregnancies (22)(23)(24). One study by Taerk et al reported that hCG administration significantly increased clinical pregnancy rates compared with monitoring of spontaneous serum LH surge in subfertile patients undergoing controlled ovarian hyperstimulation IUI cycles (22).…”
Section: Discussionmentioning
confidence: 99%